Physicochemical properties and antimicrobial impacts of plasma‐activated simulated seawater on Escherichia coli. Issue 5 (5th May 2022) - Campbell, Vashti M.; Wang, Qingyang; Hall, Steven G.; Salvi, Deepti
Abstract: Background: Some filter‐feeding molluscan shellfish can concentrate harmful bacteria in their intestines during feeding, thus posing a potential food safety risk to human consumers. Plasma‐activated simulated seawater (PASW) generated from non‐thermal plasma may help reduce bacteria in live, molluscan shellfish when used as a disinfectant in depuration systems. This study determined the physicochemical properties of PASW and its antimicrobial efficacy against Escherichia coli DH5α. These results were then compared to similar data from a plasma‐activated water (PAW) study. Results: PASW yielded temperatures ranging from 31.0 ± 0.2 to 49.7 ± 1.0°C, pH from 7.21 ± 0.0 to 2.70 ± 0.0, oxidation–reduction potential (ORP) from −15.7 ± 1.0 to 246.0 ± 0.9 mV, and electrical conductivity from 35.4 ± 0.3 to 48.1 ± 1.5 μS/cm after activation by plasma for 1–10 min. Temperature, ORP, electrical conductivity, nitrate (NO3 − ), and nitrite (NO2 − ) concentrations of PASW increased while pH decreased with increased plasma activation time. After 2‐ and 5‐min incubations, E . coli treated with PASW5 and PASW10 both resulted in the highest reductions (~3 log CFU/ml). Further, while NO3 − and NO2 − concentrations in PASW were higher than in PAW of the same plasma exposure time, PAW yielded higher E . coli reduction values across treatments. Conclusion: Results from this study demonstrate the potential of PASW as a disinfectant for live, molluscan shellfish depuration to provide a microbiologically safer seafood product for human consumers.